Fray Bartolomé de las Casas y el oficio de defensor de indios en América y en la Corte española - Caroline Cunill (Nuevo mundo - Mundos Nuevos, 2012)
The objective of the present study is to highlight the role played by Fray Bartolomé de las Casas in the process of defining the office of the defensor de indios –Defender of the Indians– in the Americas and in the Council of the Indies in Spain. We pretend to demonstrate that what was at stake was an ambitious plan aimed at improving the level of Indian representation in the colonial institutions on both sides of the Atlantic. In this political struggle, Las Casas did not act solely by himself, rather he became the center of a partisan network –among which were found clericals and civilians, Spanish and Indians–, who favored the position of defensor de indios.